Separating functions, spectral theory of graphs, and locally scalar representations in Hilbert spaces - Redchuk, I. K. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We consider the connection of the separating functions $ρ_r$ with locally scalar representations of graphs and with spectral theory of graphs.